Żona dla Australijczyka - Bareja, Stanisław (Poland : Telewizia Polska, 1964)
A very popular comedy from the 1960s, both widely acclaimed and criticized for being an “animated brochure” of communist Poland. Robert – an Australian farmer of Polish decent – is looking for a Polish wife. She needs to be thrifty and pretty. He arrives in Gdańsk and a family friend agrees to help him in the quest. Robert is short of time, though, and would like to have a wider choice. While watching the “Mazowsze” folk dance group perform, Robert falls in love with one of the dancers. The friend assures him that she can be married. He overhears another dancer's conversation and concludes that kidnapping would be the best way to win the girl’s heart. Wrongly assuming that the girl dreams about romantic abductions, he imprisons her in an luxury apartment and tries to convince her of his passion. After the misunderstanding is cleared up, Robert gives up and releases the girl. He is resigned, but she seems to start feeling for him. They meet again on a cruise, and live happily ever after.
Duration: 01:32:00
Keywords: Fiction films